TEACHER QUESTIONS IN ENGLISH CLASSROOM INTERACTION IN GRADE TWELVE SENIOR HIGH SCHOOL - Devi Novita Sari and Rita Suswati (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2017)
This study aims to find out the types of questions used by teachers and describe the use ofteacher‟s questions in the teaching-learning process. This study was conducted by usingdescriptive qualitative research design. The data source of research was the English teacher ofSMA Swasta RK Serdang Murni Lubuk Pakam. The data was the utterances of teacher thatdelivered questions. Techniques of collecting data were observation, recording and interviewing(the teacher). The result of this study showed that there were four types of questions used by theteacher during teaching-learning process with the total of questions were 130. Teacher spentfactual questions totally 55,4% (72 questions), empirical questions were totally 21,5% (28questions), productive questions were 3,1% (4 questions), and evaluative questions were 20%(26 questions). From those types, factual questions were dominantly used by the teacher. Thisstudy also found that the relation between teacher‟s questions and teaching-learning process isteacher‟s questions brought the process of classroom interaction from begin at last. Teacher‟squestions built interaction between teacher and students from pre-activity, main-activity, andpost-activity. The use of questions by the teacher was in order to get attract the students to bemore active and to see how far the students had mastered the lesson given. It can be concludedthat the teacher‟s questions are as the technique of teaching.